1985
DOI: 10.1021/bi00335a013
|View full text |Cite
|
Sign up to set email alerts
|

Release of iron from the two iron-binding sites of transferrin by cultured human cells: modulation by methylamine

Abstract: We have investigated the effect of increasing concentrations of methylamine (5, 10, and 25 mM) on the removal of iron from the two iron-binding sites of transferrin during endocytosis by human erythroleukemia (K562) cells. The molecular forms of transferrin released from the cells were analyzed by polyacrylamide gel electrophoresis in 6 M urea. Endocytosis of diferric transferrin was efficient since greater than 10% of surface-bound protein escaped endocytosis and was released in the diferric form. Although tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

1985
1985
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 40 publications
4
24
0
Order By: Relevance
“…While there are other types of iron chelators/inhibitors that can block cellular iron uptake, methylamine is commonly used to inhibit intercellular iron transport. 34,[54][55][56] Our results are further supported by the well-established transferrin-ferritin intracellular iron transport and storage mechanism. 53 Additional evidences showed that the predominant proteins, upregulated during neural stem cell differentiation, involved in iron storage (ferritin L chain) and cytoskeleton.…”
Section: Discussionsupporting
confidence: 80%
“…While there are other types of iron chelators/inhibitors that can block cellular iron uptake, methylamine is commonly used to inhibit intercellular iron transport. 34,[54][55][56] Our results are further supported by the well-established transferrin-ferritin intracellular iron transport and storage mechanism. 53 Additional evidences showed that the predominant proteins, upregulated during neural stem cell differentiation, involved in iron storage (ferritin L chain) and cytoskeleton.…”
Section: Discussionsupporting
confidence: 80%
“…Both reticulocytes and K562 cells are known to have a high rate of iron uptake, many transferrin receptors, and a high demand for iron (2,25); thus, exposure of transferrin to a pH below 6 might be expected in these cell types, resulting in the observed release of primarily apotransferrin (25)(26)(27). This hypothesis is currently under investigation using the method described here to measure the acidification kinetics in other cell types.…”
Section: Discussionmentioning
confidence: 98%
“…In a similar manner, Young and coworkers found the rate of recycling using the loss of cell-associated radiolabeled complexes as a percentage of the initial, or maximum, amount of Tf bound [102]. Therefore, Eq.…”
Section: Obtaining a Quantitative Understanding Of Tf Trafficking mentioning
confidence: 99%
“…In a similar manner, Young and coworkers evaluated the rate constant for the internalization of the holo-Tf/TfR complex, neglecting the dissociation of holo-Tf from TfR [102]. In this case, the authors measured the percentage of cell-surface complexes remaining prior to endocytosis using pronase to distinguish cell-surface bound from internalized complexes.…”
Section: Obtaining a Quantitative Understanding Of Tf Trafficking mentioning
confidence: 99%